Student Engagement and Academic Innovation as Drivers of University Entrepreneurship in Metropolitan Lima - Olórtegui Alcalde, Luis Miguel (LACCEI, 2025)
This study examines the role of student engagement and academic innovation as fundamental drivers of university entrepreneurship in Metropolitan Lima, Peru. Considering the social, economic, and educational challenges facing this region, universities are positioned as key spaces for promoting a comprehensive, transformative, and action-oriented education. Employing a quantitative, explanatory approach and a non-experimental, cross-sectional design, structural equation modeling (PLS-SEM) was applied to a sample of 385 undergraduate and graduate students involved in academic initiatives related to innovation and entrepreneurship. The findings reveal statistically significant associations between academic engagement and creativity (β = 0.61; p < 0.001), educational innovation and problem-solving (β = 0.57; p < 0.01), and entrepreneurial proactivity (β = 0.48; p < 0.05). Additionally, structural barriers were identified, including lack of methodological guidance (42%), academic overload (33%), and limited access to technological resources (23%). These limitations call for strategic actions such as integrating active methodologies into the curriculum, strengthening teacher training, and promoting inter-institutional partnerships. In conclusion, the synergy between student engagement and academic innovation enhances entrepreneurial competencies and positions universities as agents of social transformation and sustainable territorial development.